The Rohingyas : inside Myanmar's hidden genocide - Ibrahim, Azeem (Speaking Tiger, 2017)
The Rohingya are a Muslim group who live in Rakhine state (formerly Arakan state) in western Myanmar (Burma), a majority Buddhist country. According to the United Nations, they are one of the most persecuted minorities in the world. They suffer routine discrimination at the hands of neighboring Buddhist Rakhine groups, but international human rights groups such as Human Rights Watch (HRW) have also accused Myanmar's authorities of being complicit in a campaign of ethnic cleansing against the Rohingya Muslims. The Rohingya face regular violence, arbitrary arrest and detention, extortion, and other abuses, a situation that has been particularly acute since 2012 in the wake of a serious wave of sectarian violence. Islam is practiced by around 4% of the population of Myanmar, and most Muslims also identify as Rohingya. Yet the authorities refuse to recognize this group as one of the 135 ethnic groups or 'national races' making up Myanmar's population. On this basis, Rohingya individuals are denied citizenship rights in the country of their birth, and face severe limitations on many aspects of an ordinary life, such as marriage or movement around the country. This expose of the attempt to erase the Rohingyas from the face of Myanmar is sure to gain widespread attention.